Social emotional learning matters: Interpreting educators’ perspectives at a high-needs rural elementary school - Dyson, Ben; Shen, Yanhua; Howley, Donal; Baek, Seunghyun (Frontiers in Education, 2023)
Introduction School educators’ have a great influence on the adoption, sustainability, and development of school-based Social and Emotional Learning (SEL) programs. The purpose of this school-based research was to investigate educators’ experiences and perspectives on implementing SEL in a high-needs rural elementary school setting. Methods Fifteen school educators (n = 15), including ten K-5 classroom teachers, one special education teacher, one social worker, and three school leaders, participated in this study. In addition, lessons were observed, and 17 sets of field notes were taken during 17 different days of visit (60–90 min) over the two semesters. A case study design drawing on qualitative research methods was utilized. Results The inductive analysis and constant comparison of the collected data generated six themes: prerequisite for academic success, essential skills for everyday life, lack of time, lack of preparation and development, home-school disconnection, and pushback from students. Discussion The study provided qualitative evidence to support the need for quality SEL implementation and revealed nested levels of constraints for school educators’ implementing SEL from the “voices” of school educators. The study also calls for collaborative efforts and shared strategies to facilitate “legitimate” long-term partnerships between universities and schools, families, and communities, particularly in rural areas, in promoting a more holistic vision of the social and emotional development of our children.